2016
DOI: 10.1111/liv.13266
|View full text |Cite
|
Sign up to set email alerts
|

Real life Egyptian experience of efficacy and safety of Simeprevir/Sofosbuvir therapy in 6211 chronic HCV genotype IV infected patients

Abstract: Sofosbuvir/Simeprevir combination is an effective and well tolerated regimen for patients with chronic HCV genotype IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 20 publications
8
26
0
Order By: Relevance
“…These results obtained from our study are broadly consistent with the major trends of proven efficacy of such combination therapy in managing HCV as shown in several previous publications [12][13][14][15][16][17][18][19][20]. Our findings were matching with the published results of a Phase III (PLUTO) clinical trial which investigated Simeprevir in combination with sofosbuvir in treatment of naïve and experienced patients with and without compensated cirrhosis in hepatitis C virus genotype 4 infection where this combination achieved SVR rate of 100% among study subjects [12].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results obtained from our study are broadly consistent with the major trends of proven efficacy of such combination therapy in managing HCV as shown in several previous publications [12][13][14][15][16][17][18][19][20]. Our findings were matching with the published results of a Phase III (PLUTO) clinical trial which investigated Simeprevir in combination with sofosbuvir in treatment of naïve and experienced patients with and without compensated cirrhosis in hepatitis C virus genotype 4 infection where this combination achieved SVR rate of 100% among study subjects [12].…”
Section: Discussionsupporting
confidence: 93%
“…Their study reported a SVR in easy and difficult-totreat groups were 96% and 93% respectively after 12 weeks [14]. [17], while in Phase III OPTIMIST-2 study in patients with cirrhosis achieved 83% SVR12 [18].…”
Section: Discussionmentioning
confidence: 96%
“…Study characteristics were summarised in Tables and . Fifty‐six studies were included, with a total of 5522 patients with HCC, while 27 studies enrolled non‐HCC patients as control groups. Fifty‐three (95%) studies were observational cohorts (45 retrospective and eight prospective) and three studies were clinical trials.…”
Section: Resultsmentioning
confidence: 99%
“…Since then, several studies of real-life have been published. [12][13][14][15][16] One of the largest was the US-TARGET cohort, 12 which included 491 cirrhotic patients (45% with prior hepatic decompensation). Most of these patients (79.8%) received SOF/SMV without RBV.…”
Section: Introductionmentioning
confidence: 99%